Towards design rules for rectangular silo filling pressures. (1st November 2019) - Rotter, J.M.; Goodey, R.J.; Brown, C.J.
Highlights: This work shows the factors that affect wall pressure distributions in silos. A validated finite element model is used for parametric study. The importance of wall and solid stiffness is demonstrated. A relationship for wall pressures and stiffness is presented. This relationship can be used for more efficient structural design. Abstract: An experimentally validated finite element model of filling pressures in rectangular silos with flexible walls is used to predict the stress regime in the stored solid in squat and intermediate aspect ratio silos. The model predicts the state of stress in the stored solid and the pressures imposed on the flexible walls of the silo. The non-uniform horizontal pressure distributions at each depth at the end of filling are explored. It is known that an empirical relation for the horizontal pressure variation on each straight wall derived from experimental observations in an earlier study closely matches the computational predictions. The coefficients of this relation are found to vary with depth below the stored solid surface, and depend on the relative stiffness of stored solid and the silo wall. Following many calculations involving different solids, an empirical relationship is derived that is suitable for practical design for a range of different stored solids for which relevant properties are known. The resulting expression is well suited to the practical determination of filling pressures in rectangular silos, and provides a silo design pressure proposal that is based on theoretical, rather than empirical findings.